Inovasi, Komunikasi, dan Kreativitas dalam Mewujudkan Desa Wisata Watesari yang Lebih Bersinergi - Muhammad, Akbarsyah Izzulhaq; Aprillia, Chika; Nasir, Sa’diyah (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
The term village has been popular with the general public, whether physical conditions (topography, geological, hydrographic, demographic) or non-physical (mindset of citizens, ideals, lifestyles) as conservative, even primitive areas. There are many reasons that shape the paradigm of people's mindset regarding villages as underdeveloped areas, including remote geographical locations, far from technological advances, and primitive jobs, such as odd jobs, farm workers, etc. However, in recent years, the way of thinking about such villages has slowly changed because many villages have made breakthroughs in innovation that raise creativity so as to bring positive prestige about rural areas. The reconstruction of the thinking paradigm of rural communities that tend to want to advance in recent years shows a reality of the desire to compete with urban communities. The spirit of strong innovation and healthy creativity has been realized in several villages, including Watesari Village, Balongbendo District, Sidoarjo. In recent years, Watesari Village has succeeded in discovering, as well as developing an innovation that has now become a symbol of the village, namely the Star fruit. This forms the foundation of the stairs that allows Watesari Village to climb the path of success and prosperity.